Renal allograft interstitial fibrosis: multicellular interactions and therapeutic strategies - Ding, Runmin; Shen, Qinghuan; Zhou, Junyi; Tan, Ruoyun; Gu, Min; Wang, Zijie; Gui, Zeping (Frontiers in Immunology, 2026)
Kidney transplantation remains the most effective treatment for end-stage renal disease (ESRD). However, long-term graft survival is still limited by chronic allograft dysfunction (CAD), which is primarily characterized by renal interstitial fibrosis (RIF). The development of RIF is an actively regulated and progressive process involving both immune and non-immune mechanisms. Within the renal microenvironment, multiple cell populations interact to form a self-reinforcing profibrotic network that ultimately drives irreversible fibrotic remodeling. Despite increasing mechanistic insights, the precise modes of multicellular crosstalk remain incompletely understood, and effective targeted therapies are still lacking in clinical practice. In this review, we systematically summarize the dynamic interactions among immune cells, renal epithelial cells, and stromal cells during renal allograft interstitial fibrosis. By integrating recent advances at the cellular and molecular levels, we identify key regulatory nodes within this multicellular network and discuss emerging therapeutic targets and precision intervention strategies aimed at inhibiting profibrotic signaling, alleviating pathological tissue remodeling, and improving long-term graft function and survival.